UPAYA MENINGKATKAN HASIL BELAJAR TENIS MEJA MELALUI METODE PEMBELAJARAN TERBIMBING DAN DEMONSTRASI PADA SISWA KELAS VII UPT SMP NEGERI 7 SATAP SEKO - Mahamuddin Mahamuddin (Jurnal Panrita, 2020)
The purpose of this study was to improve student learning outcomes in table tennis learning in class VII students of UPT SMP Negeri 7 Satap Seko. Through guided learning methods and demonstrations. This research is a. CAR Classroom Action Research. The research was conducted in two cycles and each cycle consisted of planning, acting, observing and reflecting. The research subjects were students of grade VII, totaling 28 students 16 boys and 12 girls. The data sources came from teachers and students. The technique of collecting data is by using observation and documentation techniques. The results showed that through guided learning methods and demonstrations, it could improve student learning outcomes from cycle I and cycle II. It can be seen that the increase occurred in the first cycle of student activity and motivation and student learning outcomes increased, although not optimal. The implementation of cycle II causes student activity and motivation, and student learning outcomes or student learning completeness increases by 21.42% from cycle I of 64.29% and cycle II to 85.71%. Students 'abilities for psychomotor, affective and cognitive also increased by 20.59 students' classical average achievement of 74.29 in the sufficient category in the first cycle, to 94.88 in the excellent category in the second cycle Thus guided learning methods and demonstrations can support a very high quality learning.